2017
DOI: 10.1159/000479840
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Tolerability of Anticoagulants for Thromboprophylaxis after Major Joint Surgery: a Network Meta-Analysis

Abstract: Background/Aims: Venous thromboembolism (VTE) is the most common complication after major joint surgery. VTE can easily develop into pulmonary embolism (PE), leading to cardiopulmonary dysfunction or sudden death. We aimed to comprehensively analyse the thromboprophylactic drugs that are used to prevent thrombosis and reduce bleeding risk. Methods: We searched the PubMed, EMBASE, and Cochrane databases for randomized controlled trials that evaluated the use of thromboprophylaxis after major joint surgery. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 124 publications
1
2
0
Order By: Relevance
“…The reviewed data of major and minor postoperative complications recorded revealed that apixaban was not inferior to enoxaparin in terms of its safety and prevention of major bleeding. This finding confirms that of the study by Wang et al, 16 which concluded that apixaban was a reliable prophylaxis for thromboembolism, being able to reduce the clinical incidence of major bleeding events.…”
Section: Ta B L E 1 Surgical Wound Assessment Criteriasupporting
confidence: 91%
“…The reviewed data of major and minor postoperative complications recorded revealed that apixaban was not inferior to enoxaparin in terms of its safety and prevention of major bleeding. This finding confirms that of the study by Wang et al, 16 which concluded that apixaban was a reliable prophylaxis for thromboembolism, being able to reduce the clinical incidence of major bleeding events.…”
Section: Ta B L E 1 Surgical Wound Assessment Criteriasupporting
confidence: 91%
“…One of the most common complications after total joint arthroplasty is venous thromboembolism (VTE), and its incidence rate is relatively high. [1][2][3][4][5] Clinical trials show that the rate of deep VTE is 42% to 57% in Western countries and 23% to 42% in Japan among patients who received no antithrombotic prophylaxis after total hip arthroplasty. 6,7 The early diagnosis of VTE after joint arthroplasty is of great importance for predicting the prognosis and outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that sudoxicam, FXI-ASO (factor XI antisense oligonucleotide), and betrixaban were likely to be associated with the lowest risk of all-cause bleeding after major joint surgery. Furthermore, betrixaban, dalteparin, and warfarin were associated with the lowest risk of major bleeding/nonmajor clinically relevant bleeding events [39].…”
Section: Betrixabanmentioning
confidence: 95%